Partial Least Square Structural Equation Modeling (PLS-SEM) / Nur Zainie Abd Hamid - Abd Hamid, Nur Zainie (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Structural Equation Modeling (SEM) is a multivariate statistical analysis tool that is increasingly used to analyze structural relationship by the researcher in the business field. Two primary SEM techniques are Covariance-based Structural Equation Modeling (CB-SEM) and Partial Least Squares Structural Equation Modeling (PLS-SEM). CB-SEM is primarily used to confirm or reject theories by determining how well a proposed theoretical model can estimate the covariance matrix for a sample dataset. On the other hand, PLS-SEM is primarily used to develop theories in exploratory research by explaining the variance in the dependent variables when examining the model.